2016
DOI: 10.1186/s12917-016-0662-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucose concentration in capillary blood of dairy cows obtained by a minimally invasive lancet technique and determined with three different hand-held devices

Abstract: BackgroundDairy cows have a massive demand for glucose at the onset of lactation. A poor adaption to this period leads to an excessive negative energy balance with an increased risk for ketosis and impaired animal health and production.Besides the measurement of ketones, analysing the glucose concentration in blood is reported as helpful instrument for diagnosis and differentiation of ketosis. Monitoring metabolic parameters requires multiple blood sampling. In other species, new blood sampling techniques have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 29 publications
2
25
1
3
Order By: Relevance
“…It has been reported that in dairy cattle, adequate levels of blood glucose may be important for proper functioning of the ovaries and uterus and that blood glucose of 60 (mg/dL) is appropriate for the cow to get pregnant at first insemination [4]. In this study, blood glucose (mg/dL) levels were within normal range (40-60) [24], and that concentration of plasma glucose was higher during late pregnancy (67.89 ± 6.52) and in the PPP (65.88 ± 5.94) than in nonpregnant cows (57.40 ± 7.90). In the PPP, the serum glucose concentration was insignificantly lowered than in the pregnancy period, and this is probably due to the needs of lactose and fats for milk production [25].…”
Section: Discussionmentioning
confidence: 52%
“…It has been reported that in dairy cattle, adequate levels of blood glucose may be important for proper functioning of the ovaries and uterus and that blood glucose of 60 (mg/dL) is appropriate for the cow to get pregnant at first insemination [4]. In this study, blood glucose (mg/dL) levels were within normal range (40-60) [24], and that concentration of plasma glucose was higher during late pregnancy (67.89 ± 6.52) and in the PPP (65.88 ± 5.94) than in nonpregnant cows (57.40 ± 7.90). In the PPP, the serum glucose concentration was insignificantly lowered than in the pregnancy period, and this is probably due to the needs of lactose and fats for milk production [25].…”
Section: Discussionmentioning
confidence: 52%
“…Glucose was assayed by colorimetric method using a commercial Kit from Biodiagnostic Company (Dokki, Giza, Egypt) and UV-2100 UV/VIS Spectrophotometer (Shimadzu Corporation, Tokyo, Japan) [25]. Blood samples were classified according to its glucose level as hypo-(<40 mg/dL), normo-(40-60 mg/dL) or hyperglycemic (>60 mg/dL) [26].…”
Section: Blood Metabolitesmentioning
confidence: 99%
“…Blood concentrations of glucose in humans are approximately 5.5 mM [97]. Glucose concentrations in ruminants are typically lower (2–4 mM [98100]), and primary sources of energy are typically volatile fatty acids in the form of acetic, propionic and butyric acid [101, 102]. To date, products of volatile fatty acid metabolism, such as 2-methylcitrate and 2-methyl-cis-aconitase, have not been reported in T. congolense .…”
Section: Discussionmentioning
confidence: 99%